Alveolar paratesticular rhabdomyosarcoma mimicing epididymitis: Case report and literature review. Issue 25 (June 2018) - Lei, W-H; Wu, Wen-Feng; Zhen, Jin-Yang; Li, Yang-Hui; Li, Jie; Xin, Jun
Abstract: Rationale: Most patients with paratesticular rhabdomyosarcoma may typically present as a unilateral, painless palpable scrotum mass. However, only a few cases of RMS presenting as painful edema of the scrotum mimicing epididymitis. We herein report an unusual case of alveolar paratesticular rhabdomyosarcoma misdiagnosed as epididymitis. Patient concerns: A 19-year-old adolescent, presented to urologist with painful swelling of the scrotum on the left side over the preceding several days. Antibiotics were administered by physician for two months and the pain improved, but the swelling did not fade. Diagnoses: Alveolar praratesticular rhabdomyosarcoma. Interventions: A left, soft tissue mass in the scrotum without definite metastasis or lymphadenopathy was confirmed by computed tomography (CT) and magnetic resonance imaging. A radical left orchiectomy via the inguinal approach was performed successfully. Outcome: The patient received 8 cycles of adjuvant chemotherapy, the patient remains recurrence- and metastasis-free at 13 months after surgery. Lessons: When paratesticular RMS is presenting with symptoms of epididymitis, this malignant tumor is usually overlooked. When patients complain of painful scrotal swelling, RMS arise from paratesticular tissue should be considered.